THE TEMPERATURE DEPENDENCE OF EXCITONS SELF-TRAPPING RATE IN IODIDES OF ALKALI METALS AT LATTICE SYMMETRY LOWERING - Zhanturina, N. N.; Shunkeev, K. Sh.; Aliev, B. A. (Recent Contributions to Physics, 2017)
In the article was calculated the value of excitons self-trapping rate at lattice symmetry lowering and at different temperatures. By the theory of excitons kinetic were determined the time of excitons self-trapping,the length of free path of excitons in several alkali halides. The results are in agreement with experimental facts.
Keywords: the value of excitons